2016
DOI: 10.12659/msm.902120
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of CYP2C19 and Inhibitory Effects of Ticagrelor and Clopidogrel Towards Post-Percutaneous Coronary Intervention (PCI) Platelet Aggregation in Patients with Acute Coronary Syndromes

Abstract: BackgroundThe aim of this study was to observe the effects of genetic polymorphism of CYP2C19 on inhibitory effects of ticagrelor (Tic) and clopidogrel (Clo) towards post-percutaneous coronary intervention (PCI) platelet aggregation (IPA) and major cardiovascular events (MACE) in patients with acute coronary syndromes (ACS).Material/MethodsFrom August 2013 to March 2014, 166 patients with ACS undergoing PCI were selected. The patients were randomly grouped into the Tic group and the Clo group. IPA was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Stimpfle et al found the platelet reactivity measured of adenosine diphosphate(ADP)-induced platelet aggregation in any LOF allele and no LOF allele of CYP2C19 genotype were 12.27 ± 11.4 and 11.21 ± 7.0 AU*min ( P > 0.05), respectively [ 26 ]. Dong et al found no significant differences on the risk of death, MI, revascularization, and stroke according to CYP2C19 genotype [ 27 ]. A study conducted by Wang et al found patients with acute minor stroke or TIA carrying any CYP2C19 LOF allele were associated with an increased risk of MACEs [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stimpfle et al found the platelet reactivity measured of adenosine diphosphate(ADP)-induced platelet aggregation in any LOF allele and no LOF allele of CYP2C19 genotype were 12.27 ± 11.4 and 11.21 ± 7.0 AU*min ( P > 0.05), respectively [ 26 ]. Dong et al found no significant differences on the risk of death, MI, revascularization, and stroke according to CYP2C19 genotype [ 27 ]. A study conducted by Wang et al found patients with acute minor stroke or TIA carrying any CYP2C19 LOF allele were associated with an increased risk of MACEs [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of these studies are presented in Table 1. [20][21][22][23][24][25][26][27][28][29][30][31] A total of 12 studies encompassing 5829 CV patients with CYP2C19 LoF alleles were included in primary analysis. Patients, who were treated with clopidogrel at a dose range of 75-150 mg/day, prasugrel at a dose range of 3.75-10 mg/day, and ticagrelor at a dose of 180 mg/day, were diagnosed with stable CAD or acute coronary syndrome (ACS).…”
Section: Overviews Of Studiesmentioning
confidence: 99%
“…So với nhóm chuyển hóa giảm và kém, độ ngưng tập tiểu cầu của nhóm chuyển hóa bình thường có xu hướng thấp hơn (23,3 ±11,6% so với 27,8 ± 13,5%) phù hợp với nghiên cứu của Xinchun Yang và cộng sự [7]. Tuy nhiên sự khác biệt này chưa đạt mức ý nghĩa thống kê (p=0,169 >0,05).…”
Section: Bàn Luậnunclassified